Measuring Private Higher Education Electronic Service Quality in Bandung - Rina Indrayani (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study was to measure the quality of electronic services and examine the relationship of the dimensions of the electronic quality services to the satisfaction of the students. The data were collected by distributing questionnaires with a total sample of 293 respondents and using a quantitative descriptive approach. The data analysis used was statistical analysis in the form of multiple linear regression tests. Using analyzing by dimensional electronic Quality Service that information quality, security, website functionality, customer relationship and responsiveness and fulfillment. Furthermore, this study identifies the relationship each of these dimensions on student satisfaction. This analysis reveals that all dimensions of electronic service quality has a strong connection to the student satisfaction. So, the need to preserve electronic quality service as a form of maintaining the existing student.